Silver-controlled evolution of morphological, structural, and optical properties of three-dimensional hierarchical WO3 structures synthesized from hydrothermal method - Lopes, L. F. [UNESP] (2018)
Hierarchical structures of self-assembled three-dimensional (3D) WO3–Ag were synthesized via hydrothermal growth using precursor solutions of peroxopolytungstic acid with different amounts of Ag. The as-grown samples were analyzed by X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), thermogravimetric analysis (TGA), Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, ultraviolet–visible spectroscopy, and X-ray photoelectron spectroscopy. The XRD and Raman studies showed that as the amount of Ag was varied from 0 to 10 wt% in the hydrothermal growth solution, the crystal phase gradually changed from orthorhombic WO3·0.33H2O to hexagonal WO3. The FTIR and TGA studies revealed different hydration levels, supporting the XRD and Raman results. By controlling the amount of Ag in the precursor solution, platelet-like building blocks and hexagonal building blocks were obtained, highlighting the role of Ag in the hydrothermal growth of 3D WO3·0.33H2O and WO3 microcrystals. In addition, high-magnification FESEM images showed that the Ag nanoparticles were anchored on the surface of the 3D hierarchical WO3–Ag structures, and the UV–vis measurements demonstrated that the 3D hierarchical structures gradually absorbed more light when the Ag content was increased. Moreover, the band-gap energy decreased when the Ag content was increased from 0 wt% (Eg = 2.65 eV) to 10 wt% (Eg = 2.26 eV). These experimental results demonstrate that the amount of Ag played a crucial role in determining the building blocks' morphology, and the hydration level, optical properties, and crystal phase of the WO3·nH2O microcrystals.